Sporotrichoid cutaneous leishmaniasis: atypical form - Belda, Walter; Vale, Paulo A.; Carvalho, Caroline H. C. (International Journal of Research in Medical Sciences, 2024)
Leishmaniasis comprises a heterogeneous and extensive group of infectious and non-contagious diseases caused by protozoa of the genus Leishmania spp. It is a disease considered endemic in 92 countries, with at least 1 million new cases of integumentary forms annually. Cutaneous leishmaniasis is endemic in the tropics and neotropics. It is often referred to as a group of diseases because of the varied spectrum of clinical manifestations, which range from small cutaneous nodules to gross mucosal tissue destruction. Cutaneous leishmaniasis can be caused by several Leishmania spp. and is transmitted to human beings and animals by sandflies. Despite its increasing worldwide incidence, because it is rarely fatal, cutaneous leishmaniasis has become one of the so-called neglected diseases, In endemic countries, diagnosis is often made clinically and, if possible, by microscopic examination of lesion biopsy smears to visually confirm leishmania parasites as the cause. Cutaneous leishmaniasis often presents as an ulcerated lesion, with raised, infiltrated edges, classically described as frame-like edges at the site of the mosquito bite. We report an uncommon case of a patient who presented with a lesion on the face, sporotrichoid in appearance, and thigh, which appeared simultaneously, of clinical lesions of cutaneous leishmaniasis, laboratory-confirmed and which showed excellent clinical evolution with the use of liposomal amphotericin B.